2017
DOI: 10.1158/1535-7163.mct-16-0669
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Mechanism against Trastuzumab in HER2-Positive Cancer Cells and Its Negation by Src Inhibition

Abstract: Trastuzumab in combination with chemotherapy is the standard of care for patients with human epidermal growth factor receptor 2 (HER2)-positive breast and gastric cancers. Several resistance mechanisms against anti-HER2 therapy have been proposed. Src activation has been suggested to be responsible for the resistance of HER2-positive breast cancer. In our study, we generated four trastuzumab-resistant (HR) cancer cell lines from HER2-amplified gastric and biliary tract cancer cell lines (SNU-216, NCI-N87, SNU-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 38 publications
0
36
0
1
Order By: Relevance
“…Change of agents at the downstream of targets in PI3K/AKT pathway, such as PTEN and up-regulation of tyrosine kinase receptors are also related to trastuzumab resistance. 7,20,21,22,23 Trastuzumab inhibited cell growth by antagonizing the HER-2 signal transduction pathway. However, previous research demonstrated that elevated concentration of HER-2 in mitochondria exerted stronger trastuzumab resistance in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Change of agents at the downstream of targets in PI3K/AKT pathway, such as PTEN and up-regulation of tyrosine kinase receptors are also related to trastuzumab resistance. 7,20,21,22,23 Trastuzumab inhibited cell growth by antagonizing the HER-2 signal transduction pathway. However, previous research demonstrated that elevated concentration of HER-2 in mitochondria exerted stronger trastuzumab resistance in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, drug resistance poses a huge threat to treatment for breast cancer. Although Src inhibitors are promising in reversing resistance of HER2 antagonists in patients with HER2‐positive breast cancer, the potency of Src inhibitors is weakened by quickly acquired resistance . In our study, we first identified the mRNA expression profile in cancer cells resistant to Src inhibitor and discovered that increased PAI‐1 might contribute to Src inhibitor resistance.…”
Section: Discussionmentioning
confidence: 97%
“…Although Src inhibitors are promising in reversing resistance of HER2 antagonists in patients with HER2-positive breast cancer, the potency of Src inhibitors is weakened by quickly acquired resistance. 8,18 In our study, we first identified the mRNA expression profile in cancer cells resistant to Src inhibitor and discovered that increased PAI-1 might contribute to Src inhibitor resistance. Moreover, based on our previous findings, we further showed that PAI-1 could promote saracatinib resistance by inducing the secretion of CCL5.…”
Section: Discussionmentioning
confidence: 99%
“…The HER2‐FAK interaction allows significant signaling crosstalk between the two, where FAK is required for HER2 oncogenesis and HER2 allows for resistance to FAK‐kinase inhibitors, including phosphorylating kinase‐dead FAK (Benlimame et al, 2005; Marlowe et al, 2016). FAK activation is also involved in the acquired resistance to HER2 inhibitors, trastuzumab, and lapatinib (Huang et al, 2011; Jin et al, 2017; Yang et al, 2010). By being able to disrupt this protein–protein interaction, the effects of both HER2 and FAK on cancerous cells should be drastically limited, possibly allowing for the mitigation of cancer growth/invasion and HER2‐FAK crosstalk signaling.…”
Section: Introductionmentioning
confidence: 99%